(untitled) (Research, Society and Development, 2023)
Introduction: Chronic migraine is characterized by throbbing headache that usually occurs unilaterally or bilaterally, with attacks lasting from 3 to 72 hours in a period of 15 consecutive days. The disease has no cure, but treatments can be performed to alleviate the symptoms that accompany the strong headache such as insomnia, irritability, nausea, body aches, vomiting, anxiety, poor quality sleep, depression, and mood and appetite changes. The diagnosis is clinical, made through medical evaluation of the symptoms reported by the patient. To be diagnosed with chronic migraine, the patient must have experienced migraine attacks for 15 days or more, for at least three months, and for eight consecutive days have had migraine symptoms. General Objective: To present the drug Erenumab for the treatment of chronic migraine. Methodology: The study will be carried out descriptively by means of information surveys and data collected through scientific research published in databases such as Lilacs, Medline, Google Scholar, PubMed, and SciELO, which through the research problem, a thorough data survey will be carried out in order to obtain the results expected from the study. RESULT: By conducting the study, it is aimed to raise information about erenumab as the only treatment for episodic and chronic migraine. Conclusion: In 2019, ANVISA approved the drug erenumab, being the only specific drug for the treatment that reduces or relieves the pain caused by migraine by up to 50%.